2022
DOI: 10.3390/ijms23052705
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Breast Cancer: Where Are We Now?

Abstract: Breast cancer is the most prevalent cancer and the leading cause of cancer-related death among women worldwide. Type 2 diabetes–associated metabolic traits such as hyperglycemia, hyperinsulinemia, inflammation, oxidative stress, and obesity are well-known risk factors for breast cancer. The insulin sensitizer metformin, one of the most prescribed oral antidiabetic drugs, has been suggested to function as an antitumoral agent, based on epidemiological and retrospective clinical data as well as preclinical studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 142 publications
0
24
0
Order By: Relevance
“…Moreover, metformin may modify the expression of main pro-tumorigenic genes and exert a synergic action with chemotherapeutics in BC cells [ 83 87 ]. Therefore, metformin has been suggested as a potential antitumoral agent in BC also considering the results of epidemiological studies in both diabetic and non-diabetic women [ 20 , 26 , 88 90 ]. Cumulatively, these data recently paved the way for numerous trials aimed at investigating whether patients with diverse BC subtypes may take advantage from the use of metformin either alone or in combination with chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, metformin may modify the expression of main pro-tumorigenic genes and exert a synergic action with chemotherapeutics in BC cells [ 83 87 ]. Therefore, metformin has been suggested as a potential antitumoral agent in BC also considering the results of epidemiological studies in both diabetic and non-diabetic women [ 20 , 26 , 88 90 ]. Cumulatively, these data recently paved the way for numerous trials aimed at investigating whether patients with diverse BC subtypes may take advantage from the use of metformin either alone or in combination with chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological and retrospective clinical data have demonstrated that a first-line drug for T2D, namely metformin, is associated with a low risk of BC and reduced cancer-related mortality rate in T2D patients [ 19 – 23 ]. Accordingly, extensive preclinical studies have indicated that metformin may exert antitumor effects in BC cells through both direct (insulin-independent) and indirect (insulin-dependent) mechanisms [ 24 26 ]. One of the well-accepted insulin-independent effects of metformin involves the activation of adenosine monophosphate activated protein kinase (AMPK), which in turn downregulates main insulin-stimulated transduction pathways, such as IRS1 and PI3K/AKT/mTOR transduction signaling [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin leads to reprograming of lipid metabolism, as a hallmark of cancer, by increase in acetyl-CoA carboxylase (ACC) and fatty acid synthase (FASN), and miRNA regulation [ 58 ]. It also inhibits Complex I of the mitochondria and increases the AMP/ATP ratio which leads to further AMPK activation [ 59 ]. The anti-BC effects of metformin have been illustrated in Fig.…”
Section: Antitumor Mechanisms Of Metformin In Bcmentioning
confidence: 99%
“…Breast cancer is associated with a high mortality in women worldwide [ 1 ]. Breast cancer treatment is based on several factors, including cancer stage, size, and metastasis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%